2000
DOI: 10.3923/pjbs.2000.2033.2034
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matter Status of Gujar Khan Tehsil

Abstract: Abstract:A study was conducted to investigate the organic matter status of Tehsil Gujar Khan of district Rawalpindi. Forty eight composite soil samples were collected from different sites of Tehsil. These samples were analyzed for organic matter. Organic matter was deficient or poor <0.86% in all the soil samples analyzed. The maximum organic matter of 0.8% were recorded at Bardiana site and minimum organic matter of 0.25% were observed at Gulliana site. The average maximum organic matter of 0.6% were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The highest SOM was in the surface layer at the Himalayan piedmont, where rainfall and vegetative cover are normally higher than in the other areas. Fateh et al (2006) found SOM ranges of 0.172–0.932% in the region, and Qureshi et al (2000) reported SOM ranges of 0.25–0.8% in the tehsil (administrative district) of Gujar Khan. Figure 7 reflects a decreasing trend of organic matter towards the tehsil .…”
Section: Resultsmentioning
confidence: 99%
“…The highest SOM was in the surface layer at the Himalayan piedmont, where rainfall and vegetative cover are normally higher than in the other areas. Fateh et al (2006) found SOM ranges of 0.172–0.932% in the region, and Qureshi et al (2000) reported SOM ranges of 0.25–0.8% in the tehsil (administrative district) of Gujar Khan. Figure 7 reflects a decreasing trend of organic matter towards the tehsil .…”
Section: Resultsmentioning
confidence: 99%